The Effect of Transfer Pricing, Profitability, and Fixed Asset Intensity on Tax Aggressiveness with Audit Committee as Moderating Variable - Romita Situmorang; Andang Wirawan Setiabudi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of transfer pricing, profitability, and fixed asset intensity on tax aggressiveness, with the audit committee as a moderating variable. The object of this research is consumer cyclical and consumer non-cyclical sector companies listed on the Indonesia Stock Exchange (IDX) during a certain period. The study is grounded in corporate governance theories, particularly agency theory and stewardship theory, to explain the moderating role of the audit committee. Agency theory suggests that conflicts between managers (agents) and shareholders (principals) may lead to aggressive tax strategies to maximize short-term financial gains, whereas stewardship theory posits that strong governance mechanisms, such as an effective audit committee, can ensure ethical corporate behavior and regulatory compliance. The method used was a quantitative approach with moderated regression analysis (MRA). The data used were annual financial statements selected through the purposive sampling method. Transfer pricing, profitability, as measured by Return on Assets (ROA), and fixed asset intensity, are independent variables, while tax aggressiveness is measured using Effective Tax Rate (ETR). Transfer pricing is assessed through related-party transactions, specifically by calculating the ratio of trade receivables from related parties to total receivables, following the approach used in prior empirical studies on transfer pricing practices. The audit committee is tested as a moderating variable to determine its influence in strengthening or weakening the relationship between the independent variables and the dependent variable. The results showed that transfer pricing and profitability have a significant effect on tax aggressiveness, while fixed asset intensity does not have a significant effect. The audit committee is proven to moderate the relationship between transfer pricing and tax aggressiveness, but is unable to moderate the effect of profitability and fixed asset intensity on tax aggressiveness. Further analysis of the audit committee’s role reveals that its effectiveness in moderating transfer pricing strategies may depend on its structure, including its size, independence, and financial expertise. Companies with a larger and more independent audit committee with members possessing financial expertise may exhibit stronger oversight in curbing tax aggressiveness through transfer pricing. However, when it comes to profitability and fixed asset intensity, the audit committee’s oversight may be limited due to the nature of these financial metrics, which are more structurally embedded in a company’s financial management rather than discretionary tax strategies. These findings contribute to the financial management and corporate governance literature, particularly in understanding the dynamics of tax management in related sectors. This study also offers practical implications for companies to pay more attention to the audit committee's role in improving the supervision of transfer pricing practices to reduce excessive tax aggressiveness. Additionally, policymakers should consider enhancing regulatory frameworks to standardize audit committee effectiveness measures, ensuring that corporate governance mechanisms remain effective in mitigating aggressive tax strategies.